BAI’ AL-WAFA' STUDI KOMPARATIF ANTARA ULAMA HANAFIYAH DAN ULAMA SYAFI’IYAH SERTA IMPLEMETASINYA DI INDONESIA - Suhardi Suhardi (Ensiklopedia of Journal, 2019)
Bai 'al-Wafa' is the sale and purchase of a condition accompanied by the condition, that the goods sold can be bought back by the seller, if the specified deadline has arrived. This form of buying and selling resembles a rahn contract, seen from the side that the assets which are collateral must return to the owner of the property. However, if viewed from the side that the assets which become collateral are free to be taken advantage of by the collateral recipient, this agreement is similar to bai '. So the sale and purchase is disputed among scholars. Based on the above, the writer is interested to examine more deeply how the opinion of Hanafiyah scholars and Shafi'ite scholars about bai 'al-wafa' and its implementation in Indonesia. The purpose of this study is to explain the opinions of Hanafiyah scholars and Shafi'ite scholars about bai 'al-wafa', as well as which opinions are more relevant to the context in Indonesia. This type of research is library research and is descriptive in nature, namely by explaining the bai 'al-wafa' law contained in the book of Hanafiyah scholars and Shafi'ite scholars and then analyzed using the istinbath legal method according to the mindset and framework needed in this study. The results showed that the scholars had different opinions regarding this sale and purchase. Hanafiyah scholars believe that the bai'al-wafa 'law is permissible on the grounds of avoiding the public from usury. Whereas Shafi'i scholars say that in buying and selling there should be no requirement that the goods sold must be returned by the buyer to the original seller, because buying and selling are accompanied by conditions including buying and selling that is prohibited by sharia. In addition, they saw bai 'al-wafa' resembling the form of rahn contract.